Gender and the influence of peer alcohol consumption on adolescent sexual activity - Glen R. Waddell (Institute for the Study of Labor (IZA), 2010)
I consider the alcohol consumption of opposite-gender peers as explanatory to adolescent sexual intercourse and demonstrate that female sexual activity is higher where there is higher alcohol consumption among male peers. This relationship is robust to school fixed effects, cannot be explained by broader cohort effects or general anti-social behaviors in male peer groups, and is distinctly different from any influence of the alcohol consumption of female peers which is shown to have no influence on female sexual activity. There is no evidence that male sexual activity responds to female-peer alcohol consumption.
Keywords: J13; I12; 330; Sex; alcohol; adolescent; peer; risky behavior; Jugendliche; Sexualität; Alkoholkonsum; Risikopräferenz; Soziale Gruppe; Geschlecht; USA